2016
DOI: 10.1039/c5ta10032a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser-assisted synthesis of hydrogenated molybdenum oxides for flexible organic solar cells

Abstract: A novel method to synthesize a hydrogenated molybdenum oxide (H y MoO 3Àx ) thin film by irradiation of photons using a KrF laser (l ¼ 248 nm) on an ammonium heptamolybdate ((NH 4 ) 6 Mo 7 O 24 $4H 2 O) precursor layer is demonstrated. The laser-assisted synthesis is simple, and can be conducted in an ambient atmosphere without damaging the underlying bottom electrode and plastic substrate. The exposure time (30 ns) is extremely short compared to thermal annealing (>3 min). Because the highenergy photons are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The band at 962 cm −1 is assigned to the stretching vibration of terminal oxygen (OMo), whereas the peak at 733 cm −1 is attributed to the MoOMo vibrations of MoO 3 . When the MoO 3 is reduced with hydrogen, two new bands appear at 1141 and 3300 cm −1 , which are attributed to MoOH and OH vibration modes, respectively . In addition, the 1 H magic‐angle spinning (MAS) NMR results have been provided to further prove the formation of the H‐doped MoO 3 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The band at 962 cm −1 is assigned to the stretching vibration of terminal oxygen (OMo), whereas the peak at 733 cm −1 is attributed to the MoOMo vibrations of MoO 3 . When the MoO 3 is reduced with hydrogen, two new bands appear at 1141 and 3300 cm −1 , which are attributed to MoOH and OH vibration modes, respectively . In addition, the 1 H magic‐angle spinning (MAS) NMR results have been provided to further prove the formation of the H‐doped MoO 3 .…”
Section: Resultsmentioning
confidence: 97%
“…The spectrum of the pristine MoO 3 shows distinct absorption bands at 962 and 733 cm −1 . The band at 962 cm −1 is assigned to the stretching vibration of terminal oxygen (OMo), whereas the peak at 733 cm −1 is attributed to the MoOMo vibrations of MoO 3 . When the MoO 3 is reduced with hydrogen, two new bands appear at 1141 and 3300 cm −1 , which are attributed to MoOH and OH vibration modes, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…i) Change in photoconversion efficiency (PCE) by bending cycles at a radius of 0.48 cm. f–i) Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
“…Among TMOs, molybdenum oxide (MoO 3 ) has emerged as a promising candidate due to high transmittance, better air stability, and high work function (WF) . Dong et al suggested that by adopting a combination of solution processing and laser direct writing roll‐to‐roll fabrication along with the simultaneous patterning of the HTL material could be enabled (Figure f). They considered laser irradiation an alternative approach to create oxygen vacancies in MoO 3 for improving the electrical conductivity necessary for high HTL efficiency.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
See 1 more Smart Citation